Knowledge, Awareness & Practice about Cross Contamination Control among the Students of Dentistry - Nousheen Khan, Syed Midhat Batool, Muhammad Ali, Muhammad Ahmed, Asif Noor, Javeria Afzal (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Cross contamination is stated as “Spread of infection between staff members & patients in clinical setting”. Cross infection throughout clinical training might occur with transfer of infectious agents between health workers & patients in a clinical location. Dental care workers including dental assistant & doctors are at giant risk of receiving infection. Aim: To assess the awareness/knowledge & practice about cross contamination control among students of dentistry Study design: Cross-sectional study Place and duration of study: This study of 3 months duration was carried on students of Multan dental college Multan. Methodology: 60 students willingly participated in our study. Simple random sampling technique was utilized in order to collect the data. Well-structured Performa was consumed. Informed consent was sign up from the partakers. Results: 85% participants consider that dental clinics/hospitals are more predisposed to the infection/contamination than other medical fields. 90% of the partakers were totally aware about universal precautions to avert the cross contamination. All the subjects usually maintained the additional precautions while treating AIDS & hepatitis B, C patients. Majority of the partakers use gloves as well as facemask but googles or Protective eyewear, head caps & aprons were not in use by most of participants. Conclusion: Participants of our study showed adequate & sufficient awareness/knowledge but less satisfactory practice about contamination control. Knowledge gained should also be transferred into daily routine practice